Secondary traumatic stress and compassion satisfaction mediate the association between stress and burnout among Korean hospital nurses: a cross-sectional study - Hyangkyu Lee; Wonhee Baek; Arum Lim; Dajung Lee; Yanghee Pang; Oksoo Kim (BMC, 2021)
Abstract Background Burnout among nurses is a worldwide public health epidemic that adversely affects nurses' quality of life as well as the patient's outcomes. The aim of this study was to evaluate the influence of stress on nurses' burnout and to identify the mediating effects of secondary traumatic stress and compassion satisfaction among clinical nurses in South Korea. Methods A quantitative, cross-sectional study evaluated the survey data from 10,305 female registered hospital nurses who participated in the Korea Nurses' Health Study (KNHS) Module 5. The survey included a demographic questionnaire and the Professional Quality of Life version 5 (ProQOL 5). Bootstrap analyses (using the PROCESS macro) were employed to evaluate the mediating effect between variables. Results Stress was significantly associated with burnout and mediated by secondary traumatic stress and compassion satisfaction (βindirect 1 = 0.185, Bootstrap confidence interval (BS CI) [0.175, 0.194]; βindirect 2 = 0.226, BS CI [0.212, 0.241], respectively). In addition, the magnitude of the indirect effects of compassion satisfaction was significantly greater than the magnitude of the indirect effects of secondary traumatic stress (βindirect 1-βindirect 2 = − 0.042, BS CI [− 0.058, − 0.026]). The findings of this study indicate that the positive aspect (compassion satisfaction) of work experiences can offset the negative aspects (secondary traumatic stress), consequently reducing burnout level. Conclusions Our study findings suggest that a multidimensional approach to assessing nurse burnout and implementation of proper management will improve quality of life for nurses and help maintain positive attitudes and quality of patient care.